NETWORK DENSITY OF SURFACE METEOROLOGICAL STATIONS IN THE REPUBLIC OF BELARUS. IMPACT ON THE QUALITY AND ACCURACY OF OBSERVATIONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The analysis of the surface network of meteorological observations of the Republic of Belarus is given, taking into account the basic requirements and regulations of the World Meteorological Organization, as well as the methodology of the Russian Hydrometeorological Service. The zoning of the territory of the Republic of Belarus was carried out with the allocation of informatively homogeneous meteorological zones and the comparison of the results with the physical and geographical zoning. The information content of each of the homogeneous zones is assessed from the point of view of a multi-element objective analysis of the fields of the main meteorological parameters (air temperature and humidity, precipitation, wind speed, etc.).
Keywords: network of meteorological stations; network density index; optimization; minimum number of observation points; meteorological parameters; zoning of the territory